The prediction of attitude towards cheating based on spiritual intelligence and achievement goal orientation in students - maryam sheykh; Solmaz Dabiri (مطالعات روانشناسی تربیتی)
The purpose of this study was to predict attitude towards cheating based on spiritual intelligence and the achievement goal orientation (mastery-approach, mastery-avoidance, performance-approach and performance-avoidance) in students. The method of this research was descriptive correlation type. The statistical population of the present study included all female students of the first secondary level in the 15th district of Tehran in the academic year of 2022-2023 who were studying in the fields of math physics, experimental sciences, and humanities. Among 3500 community members, 245 students were selected as the research sample based on the Krejcie and Morgan table and by random sampling method. Research tools included questionnaires of Elliot and McGregor's (2001) achievement goal orientation, Frasat's academic cheating (2012) and King's intellectual intelligence (2008). The results showed that there was a negative and significant relationship between spiritual intelligence and goal orientation (mastery-approach, mastery-avoidance) with the attitude towards cheating, and there was a positive and significant relationship between performance-approach and performance-avoidance with the attitude towards cheating (p0/01). Also achievement goal orientation (mastery-approach, performance-approach and performance-avoidance) and spiritual intelligence together could predict 40% of the variance of attitude towards cheating (p0/001). Based on the findings of the research, it is necessary to investigate and intervene about the basic variables such as spiritual intelligence and the goal-orientation that affect the attitude towards cheating, in order to provide a basis for promoting and improving academic performance and reducing academic cheating.